High performance computing for computational science -- VECPAR 2014 : 11th International Conference, Eugene, OR, USA, June 30-July 3, 2014, Revised selected papers /: 11th International Conference, Eugene, OR, USA, June 30-July 3, 2014, Revised selected papers. (2015) - Unknown
No abstract available